Analysis of Critical Thinking Skill on Self-efficacy through Differentiated CBL-STEM Integrated AI-website - Arifadewi, Alyana Aurellia Putri; Ardiansyah, Adi Satrio; Fahrudi, Amir (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2026)
Society 5.0 requires adaptive learning amid rapid digital change, one of which involves integrating AI-websites. Therefore, this study aims to measure the quality of differentiated CBL-STEM using AI-website, examine the influence of self-efficacy on critical thinking skills, and describe students’ critical thinking skills based on their groups of self-efficacy. A mixed-method approach with sequential explanatory design was employed. The population in this study was all eighth-grade students at SMP Negeri 3 Ungaran, with a research sample consisting of an experimental and control group. The quantitative findings indicate that the learning tools achieved an average validation score of 91.05% (very good), and the average learning implementation score reached 84.05% (very good). In addition, the learning model effectively enhance critical thinking skills, with average posttest score of 82.26 and N-Gain of 0.759 (high category). Thus, this learning method is valid, practical, and effective in providing quality learning. Regression analysis revealed that self-efficacy has contributed 38.9% to students’ critical thinking skills. The interview results show all self-efficacy groups were able to meet the analysis indicator well, although variations were found in the fulfillment of other critical thinking indicators. This study is expected to open opportunities for more in-depth analysis of similar research.